Consumersʹ attitudes, motives and behaviour towards organic yoghurt in Croatia - Marina Tomić Maksan; Milna Tudor Kalit; Anamarija Pavlina; Željka Mesić (Mljekarstvo)
The organic food market is constantly growing, while organic yoghurt belongs to the category of the best-selling organic products in the dairy products group. The aim of this study was to determine consumer behaviour in the purchase and consumption of organic yoghurt, attitudes concerning organic yoghurt, and motives for organic yoghurt purchase. An online survey was conducted among organic yoghurt buyers. More than a third of respondents buy and consume organic yoghurt two to three times a month. Respondents buy most often organic yoghurt made from cow's milk, in plastic packaging, in supermarkets and specialty stores. The most important motives for buying organic yoghurt are health, nutritional value, and food safety. Respondents have positive attitudes about organic yoghurt. The results of this research are useful for organic food producers, (especially organic yoghurt producers) in planning and improving production, and also for food marketing experts in designing and implementing promotional activities.